The Effects of Managerial Shareholding on Audit Fees: Evidence from Hong Kong. (10th December 2012) - Lin, Z. Jun; Liu, Ming
Abstract : This study investigates how managerial shareholding affects audit pricing for listed companies in Hong Kong. Based on agency theory, we examine the relationship between managerial shareholding and audit fees, from the perspectives of the alignment effect and the entrenchment effect. We posit a non‐linear relationship, which is tested by grouping sample firms into three levels of managerial shareholding: low, intermediate, and high regions of management ownership. The empirical results reveal that the association of managerial ownership with audit fees is non‐linear: managerial shareholding is significantly and negatively associated with audit fees in the low and high regions of managerial ownership, whereas the association is significantly positive in the intermediate region. These correlations are further confirmed by the results of curvilinear regression analysis.